2018
DOI: 10.1002/ejlt.201700468
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Linoleic and Alpha‐Linolenic Ratios and Concentrations on In Vitro Endothelial Cell Responses

Abstract: Although many studies have found that two essential fatty acids, linoleic acid (LA; n‐6 polyunsaturated fatty acid, PUFA) and α‐linolenic acid (ALA; n‐3 PUFA), are closely related to the occurrence and development of cardiovascular disease (CVD), the effects of LA and ALA ratios and concentrations on CVD risk are not well known. The aim of this study is to investigate the effects of various LA/ALA ratios (1:1, 5:1, 10:1, and 20:1) and their concentrations on inflammation, oxidative stress, endothelial cell fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…In contrast, limited knowledge exists on the underlying biological effects on inflammatory processes when cells are exposed to a combination of PUFAs. However, a recent study by Yang et al examined various LA:ALA ratios (1:1, 5:1,10:1 and 20:1) on markers of inflammation, oxidative stress and cell function in endothelial cells and found no appreciable differences in IL-6 and TNF-α concentrations across ratios of LA:ALA in unstimulated cells [25]. In contrast, a previous animal study found that rats fed a high-fat diet based on plant oils with resulting in a low n-6:n-3 PUFA ratio (1:1 and 5:1) had lower serum levels of IL-6, TNF-α and C-reactive protein (CRP) compared with rats fed with a high n-6:n-3 PUFA ratio (20:1) diet [26].…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, limited knowledge exists on the underlying biological effects on inflammatory processes when cells are exposed to a combination of PUFAs. However, a recent study by Yang et al examined various LA:ALA ratios (1:1, 5:1,10:1 and 20:1) on markers of inflammation, oxidative stress and cell function in endothelial cells and found no appreciable differences in IL-6 and TNF-α concentrations across ratios of LA:ALA in unstimulated cells [25]. In contrast, a previous animal study found that rats fed a high-fat diet based on plant oils with resulting in a low n-6:n-3 PUFA ratio (1:1 and 5:1) had lower serum levels of IL-6, TNF-α and C-reactive protein (CRP) compared with rats fed with a high n-6:n-3 PUFA ratio (20:1) diet [26].…”
Section: Discussionmentioning
confidence: 98%
“…Namely, walnuts contain considerable amounts of L-arginine, which is the precursor amino acid for NO biosynthesis (Xiao et al 2018) and improves serum NO level (Joukar et al 2017). The effects of LA and ALA, highly represented in walnut kernel, on endothelial cell functions and the related gene expression are influenced by LA/ALA ratios and their concentrations, and the mechanism may be partially mediated through NO/eNOS signalling pathways (Yang et al 2018). On the other hand, eNOS-derived NO blocks Ca 2+ influx through the sarcolemmal LTCC in cardiac myocytes (Farah et al 2018).…”
Section: Protein Kinasesmentioning
confidence: 99%
“…An in vitro study on endothelial cells confirmed the beneficial effect of a low LA/ALA ratio (1:1) on cardiovascular risk but only at a low PUFA concentration, whereas the same low LA/ALA ratio might raise the risk of cardiovascular diseases at a high PUFA concentration [ 46 ]. The effects of LA/ALA ratios on endothelial function might depend on proinflammatory factors, since a low LA/ALA ratio upregulated the nuclear factor κB (a key factor in inflammatory response in atherosclerosis) gene at a high PUFA concentration [ 46 ]. Therefore, the high PUFA concentration provided to rabbits with flaxseed-rich diets in our study might change the effect of the low LA/ALA ratio in W86 flaxseed to promote atherosclerosis via enhancing the inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…The mentioned in vitro study involving endothelial cells indicated different effects of the LA/ALA ratios on the NO level, depending on PUFA concentration, with no effect on the endothelin-1 (ET-1) level [ 46 ]. Although a low LA/ALA ratio raised the eNOS gene expression, the same low LA/ALA ratio caused a decrease in the NO/ET-1 and NO levels compared to a higher LA/ALA ratio at a high PUFA concentration.…”
Section: Discussionmentioning
confidence: 99%